(untitled) (Research, Society and Development, 2021)
Cancer is not limited to the physical dimension, but it also affects the entire biopsychosocial context in which the patient is inserted, making him more susceptible to psychiatric disorders such as depression and anxiety. These often require pharmacological intervention, and the use of psilocybin, a substance found in mushroom species, is one of the alternatives considered today. The present study aims to carry out an integrative review regarding the use of alternative therapies, in this case Psilocybin, in cancer patients suffering from anxiety and / or depression disorders. The type of study carried out was an integrative literature review, which was based on a bibliographic survey of texts published between 2010 and 2021 on the PubMed platform. This survey took place between December 2020 and February 2021, with a review of three articles in total. Studies show a potential new line of alternative treatment for anxiety and depression in cancer patients, the use of psilocybin. The treatment is done quickly, sustained and lasting, in conjunction with psychotherapy there is improvement in a single dose. All the studies analyzed so far have been shown to be effective for the treatment of anxiety and depression in cancer patients. With this, psilocybin can be an alternative therapy for those patients in psychological distress due to cancer, especially for those who did not obtain a satisfactory response with the use of conventional treatment, allowing that in the future the substance may become a definitive therapeutic modality for patients in psychological distress due to cancer.